Poligami tanpa izin istri pertama menurut Hanafiyah dan Syafi’iyah serta Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan - Hannan, Abd; Rosid, Abdul (Prodi Hukum Keluarga Islam Fakultas Syari'ah Universitas Islam Zainul Hasan Genggong Probolinggo, 2024)
Polygamy is a controversial issue within Islamic discourse, with differing opinions (ikhtilaf) that have persisted for a long time. Historically, polygamy has deep roots in Islamic tradition. Before the advent of Islam in the Arabian Peninsula, polygamy was a common cultural practice among Arab societies, often with no restrictions. Islam later imposed limitations and set specific conditions for its permissibility. The ongoing debate about polygamy arises from differing interpretations by scholars of religious texts, making it a highly contentious topic that is difficult to reconcile. In Indonesia, marriage is generally based on the principle of monogamy, though polygamy is not entirely prohibited. According to Article 1 of the 1974 Marriage Law and the Compilation of Islamic Law (KHI), polygamous marriages are permitted under certain conditions. One key requirement is obtaining the consent of the first wife, which must be documented in writing. If a man practices polygamy without the first wife's consent, it can lead to significant conflict and psychological distress within the household. The wife may feel betrayed and may seek a divorce, often suffering emotionally and financially. Additionally, if the wife initiates the divorce due to unapproved polygamy, she may not be entitled to compensation (mut'ah), which further disadvantages her.